Effect of Water Temperature on the Depletion of Eugenol in Sea Bass under the Simulated Settings in Handling and Transport - Changliang Ke (MDPI AG, 2021)
The edible safety of eugenol-treated fish is one of the concerns limiting the anesthetic applied in the aquaculture industry. The depletion of eugenol was investigated at different water temperatures under the simulated settings of sea bass handling and transport. Sea bass was exposed to eugenol at a concentration of 60 mg/L for 3 min, then immediately transferred to clean water to be purged for 24 h and sampled at different time intervals. The left fish were re-exposed to eugenol in a repeat of the first exposure, purged for 48 h in clean water, and sampled for eugenol detection. Under the simulated settings, the sea bass could accumulate more eugenol residue in fillet when exposed to water at a temperature of 20 °C than that at 13 °C. However, eugenol could be depleted much faster when the sea basses were exposed to the higher water temperature. The half-lives of eugenol in sea bass were 0.28 h and 0.29 h for the first and second purging stage at a water temperature of 20 °C, while at 13 °C, the half-lives were 2 and 4.5 h, respectively. Therefore, increasing the water temperature may be an effective way to accelerate eugenol depletion in fish fillet and reduce exposure risk for the consumer.